The 1-aminocyclopropane-1-carboxylic acid deaminase-producing Streptomyces violaceoruber UAE1 can provide protection from sudden decline syndrome on date palm - Alwahshi, Khawla J.; Purayil, Gouthaman P.; Saeed, Esam Eldin; Abufarajallah, Haneen A.; Aldhaheri, Shama J.; AbuQamar, Synan F.; El-Tarabily, Khaled A. (Frontiers in Plant Science, 2022)
In the United Arab Emirates (UAE), sudden death syndrome (SDS) is one of the major fungal diseases caused by Fusarium solani affecting date palm plantations. To minimize the impact of the causal agent of SDS on date palm, native actinobacterial strains isolated from rhizosphere soils of healthy date palm plants were characterized according to their antifungal activities against F. solani DSM 106836 (Fs). Based on their in vitro abilities, two promising biocontrol agents (BCAs), namely Streptomyces tendae UAE1 (St) and Streptomyces violaceoruber UAE1 (Sv), were selected for the production of antifungal compounds and cell wall degrading enzymes (CWDEs), albeit their variations in synthesizing 1-aminocyclopropane-1-carboxylic acid (ACC) deaminase (ACCD). Although both isolates showed antagonism when applied 7 days before the pathogen in the greenhouse experiments, the ACCD-producing Sv was relatively superior in its efficacy against SDS over the non-ACCD-producing St. This was evident from the symptoms of SDS in diseased date palm seedlings which were greatly reduced by Sv compared to St. On a scale of 5.0, the estimated disease severity indices in Fs-diseased seedlings were significantly (P<0.05) reduced from 4.8 to 1.5 and 0.5 by St and Sv, respectively. Thus, the number of conidia of Fs recovered from plants pre-treated with either BCAs was comparable, but significantly (P<0.05) reduced compared to plants without any BCA treatment. In addition, a significant (P<0.05) decrease in ACC levels of both root and shoot tissues was detected in Sv+Fs seedlings to almost similar levels of healthy seedlings. However, in planta ACC levels highly increased in seedlings grown in soils infested with the pathogen alone or amended with St prior to F. solani infestation (St+Fs). This suggests a major role of ACCD production in relieving the stress of date palm seedlings infected with F. solani; thus, supporting the integrated preventive disease management programs against this pathogen. This is the first report of effectively rhizosphere actinobacterial BCAs to provide protection against SDS on date palm, and to help increase agricultural productivity in a more sustainable manner in the UAE and the region.